Survei Konsumsi Digital dan Literasi Media Warga Koto Mambang - Ridho Saputra; Malta Nelisa; Muhammad Fauzan; Tarisa Adestri; Erli Elviana; Intan Dafriani (Jurnal Intelek Dan Cendikiawan Nusantara, 2025)
This study aims to describe the patterns of digital consumption and the level of media literacy among the residents of Koto Mambang Village. Using a descriptive quantitative approach, data were collected through structured questionnaires distributed to 31 randomly selected respondents aged 15 years and above, complemented by brief interviews with selected participants. The findings indicate that internet usage is relatively high, with most respondents purchasing data packages monthly. WhatsApp emerged as the most dominant platform, followed by TikTok, YouTube, and Instagram. In terms of information literacy, over half of the respondents demonstrated critical awareness by verifying the truth of information before sharing it, while a smaller portion still relied on others’ opinions or spread information without verification. Although nearly half of the participants were familiar with fact-checking methods, a significant proportion remained unaware or only partially understood how to implement them. These results highlight that digital literacy in Koto Mambang Village has developed, yet disparities in knowledge and verification practices persist. Further educational initiatives are necessary to strengthen media literacy skills, particularly through participatory training programs that provide practical guidance on verifying online information